Enhancer RNA SLIT2 Inhibits Bone Metastasis of Breast Cancer Through Regulating P38 MAPK/c-Fos Signaling Pathway - Li, Peng; Lin, Zhiping; Liu, Qianzheng; Chen, Siyuan; Gao, Xiang; Guo, Weixiong; Gong, Fan; Wei, Jinsong; Lin, Hao (Frontiers in Oncology, 2021)
Background Breast cancer (BRCA) is the most common cancer in women while the bones are one of the most common sites of metastasis. Through new diagnostic methods or radiation or chemotherapies and targeted therapies has made huge advances, the occurrence of bone metastasis also linked with poorer survival. Enhancer RNAs (eRNAs) has been demonstrated participating in the progression of tumorigenesis and metastasis. However, the role of eRNAs in BRCA bone metastasis remains largely unclear. Method Gene expression profiling of 1211 primary BRCA and 17 bone metastases samples were retrieved from the TCGA database and the significant prognostic eRNAs were identified by Cox regression and LASSO regression. The acceptable accuracy and discrimination of the nomogram was indicated by the ROC and the calibration curves. Then target genes of eRNA, immune cells percentage by CIBESORT analysis, immune genes by ssGSEA, hallmark of cancer signaling pathway by GSVA, and RPPA protein chip were used to build a co-expression regulation network and identified the key eRNAs in bone metastasis of BRCA. Finally, CCK8 assay, cell cycle assay, and transwell assay were used to study changes in cell proliferation, migration and invasiveness. Immunoprecipitation assay and western blotting were used to test the interaction and the regulation signaling pathways. Results The 27 hub eRNAs were selected, and a survival-related linear risk assessment model with a relatively high accuracy (AUC: 0.726) was constructed. In addition, seven immune-related eRNAs (SLIT2, CLEC3B, LBPL1, FRY, RASGEF1B, DST, ITIH5) as a prognostic signature for bone metastasis of BRCA were further confirmed by LASSO and multivariate Cox regression and CIBESORT analysis Finally, in vitro assay demonstrated overexpression of SLIT2 reduced proliferation and metastasis in BRCA cells. Using high throughput co-expression regulation network, we identified that SLIT2 may regulating P38 MAPK/c-Fos signaling pathway to promote the effects of metastasis. Conclusion Based on the co-expression network for bone metastasis of BRCA, we screened key eRNAs to explore a prognostic model in predicting the bone metastasis by bioinformatical analysis. Besides, we identified the potential regulatory signaling pathway of SLIT2 in BRCA bone metastasis which provide a promising therapeutic strategy for metastasis of BRCA.